New Zealand aid and the development of class in Tonga : an analysis of the banana rehabilitation scheme : a thesis submitted in partial fulfilment of the degree of Master of Arts, Department of Sociology, Massey University - Needs, Andrew P (Massey University, 1988)
This thesis examines the bilateral aid relationship between New Zealand and Tonga. Its central purpose is to examine the impact aid is having in transforming Tongan society. This involves a critique of both development theory and of New Zealand government aid principles. The understanding of development and the application of aid by the New Zealand Ministry of Foreign Affairs remains greatly influenced by the modernisation school of thought, which essentially blames certain supposed attributes of Third World peoples for their lack of development. Dependency theorists challenged this view, claiming that Third World poverty was a direct result of First World exploitation through the unequal exchange of commodities. This has had some influence on the use of aid as a developmental tool, but has failed to supercede modernisation theory as the dominant ideology. The theory of articulation of modes of production transcends the problems of both modernisation and dependency schools. Its main thrust is that the capitalist (First World) mode of production does not immediately dominate the non-capitalist (Third World) mode but rather interacts with it. Such a conception takes cognisance of the influence of indigenous modes in creating new social formations. This is demonstrated through an analysis of the New Zealand financed Banana Rehabilitation Scheme of Tonga. In order to understand the effect of New Zealand funded aid projects in Tonga, the Banana Rehabilitation Scheme, the largest project funded at present, was used as a case study. The research method demanded a fieldwork component which entailed three months in Tonga in order to collect both historical and archival data only available there. The main fieldwork component was a series of interviews with a cross section of scheme members and other significant actors related to the scheme. This study of the Banana Rehabilitation Scheme shows that the redistributive aims Of New Zealand aid have been undermined by a greater concern with productivity. Emphasis upon the latter has meant that the project has been reoriented in favour of giving greater assistance to those who can produce bananas most easily, those who already had access to land, capital and labour. This category of growers is as much a product of the indigenous social structure of Tonga as of forces impinging from outside. Although through the banana scheme large amounts of money are being pumped into the Tongan economy, its redistributive effects are minimal. The structure of the scheme is such that many of the major benefits accrue to the already advantaged.
Keywords: Tonga; Economic assistance; Banana trade; Social classes; New Zealand